A new zero voltage transition interleaved flyback converter - Majid Delshad; Mohammad Reza Amini; Zahra Peiravan (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
The paper introduced a new zero voltage transition (ZVT) interleaved flyback converter which has two similar flyback converters. Two flyback converters are in parallel connection and auxiliary circuit in this converter provides ZVT condition for all of the main switches and also provides zero current switching and zero voltage zero current switching (ZVZCS) conditions for the auxiliary switch. Also, ZCS conditions are created for diodes turning off, so reverse recovery problem is solved. The auxiliary circuit in the suggested converter is modular, and by adding parallel branches to the flyback circuit, this circuit can provide soft switching conditions for all switches without significantly change. A complete analysis of the converter is provided and its operating intervals are explained. A 180 W laboratory prototype of the converter is made to approve the theoretical calculations. The experimental results show 7.7% increase in efficiency.